Transport-related social exclusion among secondary school students in different sub-regions of Lower Silesia, Poland: An activity-based approach - Krysiński, Dawid; Szczepański, Jacek (Quaestiones Geographicae, 2025)
While youth are generally considered to be at risk of transport-related social exclusion, only a few studies have focused on their experiences in Eastern European regions undergoing rapid neoliberal transformation of public services, including public transport systems. To address this gap, our study highlights the specific challenges faced by youth in three sub-regions of post-communist Poland, a country where neoliberalisation has led to the closure of 50% of public bus companies and around 30% of railway lines. Using an activity-based approach and the relational concept of transport-related social exclusion, we compared participation in different activities among 635 secondary school students who use different modes of transport. Our results, based on cross-tabulation analysis and ordinal regression, show that students who mainly use private cars participate in more activities than those who use other modes of transport. This effect is similar in all sub-regions, suggesting a common background of the exclusion. Simultaneously, the lowest level of activity was identified in peripheral areas. These areas were also characterised by a notable correlation between negative household economic assessments, reduced participation in activities, and lower car use. Further analysis also suggests that improvements in the frequency and routes of public transport could better meet the needs of non-car users and increase their opportunities for participation and social integration.